2012
DOI: 10.1167/iovs.11-8936
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Hypoxia-Inducible Factor-1 Knockout in the Retinal Pigment Epithelium on Choroidal Neovascularization

Abstract: PURPOSE. Hypoxia-inducible factor (HIF)-1 is a key oxygen sensor and is believed to play an important role in neovascularization (NV). The purpose of this study is to determine the role of retinal pigment epithelium (RPE)-derived HIF-1a on ocular NV. METHODS.Conditional HIF-1a knockout (KO) mice were generated by crossing transgenic mice expressing Cre in the RPE with HIF-1a floxed mice, confirmed by immunohistochemistry, Western blot analysis, and fundus fluorescein angiography. The mice were used for the oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 44 publications
3
34
0
Order By: Relevance
“…Lin et al knocked out HIF-1α in the RPE using the cre/lox system and suggested that RPE-derived HIF-1α plays a critical role in CNV [32]. Kurihare et al demonstrated the off-target effects resulting from the specific knockout of the VEGF gene in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al knocked out HIF-1α in the RPE using the cre/lox system and suggested that RPE-derived HIF-1α plays a critical role in CNV [32]. Kurihare et al demonstrated the off-target effects resulting from the specific knockout of the VEGF gene in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, an important role for expression of HIF-1 in RPE cells and CNV has been demonstrated. 26 It is also possible that other factors such as age, insulin-like growth factor 1, inflammatory cytokines, transforming growth factor b, 1,5-7 and adrenergic signaling contribute to VEGF expression in CNV. The results of our study with adrenergic blockade suggest adrenergic signaling is one of the specific contributors to alterations in the ocular angiogenic balance and CNV.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that curcumin suppress the activation of NF-κB in the RPE-choroid complexes with CNV, which is consistent with the results of previous reports. HIF-1α, the main reactor of hypoxia, can activate the transcription of various angiogenic genes including VEGF and ICAM-1, and plays a pivotal role in angiogenesis [81]. HIF-1α expression was detected in surgically excised human CNV membranes [82][83] and its level elevated in the eyes of laser induced CNV animal models (23, 18032914, 22915031) [23], [81][84].…”
Section: Discussionmentioning
confidence: 99%